Pertanggungjawaban Pidana Kecelakaan Lalu Lintas Akibat Pengemudi Mabuk dalam Perspektif Hukum - Martiasari, Andin; Maulida, Maulida; Pasaribu, Agnes; Soetijono, Irwan Kurniawan (PMIH Untag Semarang, 2025)
Traffic accidents caused by drunk drivers are a complex legal issue in the criminal justice system in Indonesia. This study aims to analyze criminal liability for drivers who drive drunk and cause accidents, as well as review legal considerations in Supreme Court Decision Number 177 K/Pid/2022. This research uses a normative juridical method with a legal and case approach. The results of the study show that even though the defendant is proven guilty under Article 310 paragraph (3) of the LLAJ Law, the sentence imposed by the judge is lighter than the maximum threat stipulated in the law. This raises a debate about the effectiveness of sanctions in providing a deterrent effect. In conclusion, this case shows a gap in the justice system that allows for lighter sentences even though there is an element of deliberate and knowingly possible in the defendant's actions